Recrafting career selves: International relocation and accompanying partners - Vidwans, Mohini; Du Plessis, Rosemary (New Zealand Sociology, 2025)
This article examines the experiences of 21 women and men in dual career couples whose intimate partners relocated to Aotearoa/New Zealand for professional and managerial work. It investigates the challenges they encountered, the strategies they adopted and the impacts of international relocation. Thematic analysis, utilising NVivo software, enabled the coding of interview material to identify trends in the accompanying partners’ narratives. The research was informed by theorising about the recrafting of selves, especially career selves, and intersections of governmentality and participants’ perceptions of agency during the transition to life in a new country. As transnational mobility of highly qualified women employees intensifies, this investigation extends literature about the experiences of accompanying partners, the complexity of contemporary gendered practices and the sense making of those involved in international relocation.